HOW TO GREEN PRODUCT AND ETHICAL LIVING FOR ZILENIAL GENERATION LADYNABILITY IN SURABAYA CITY ? - Jannah, Nur; Endah Muliatie, Yurilla (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2023)
The purpose of this study was to analyze green products, ethical living of sanitary napkins for the zillennial generation and the impact of using sanitary napkins when women of the zilenil generation buy environmentally friendly products. A descriptive qualitative research approach using the case study method. Data collection techniques through interviews, observation and documentation using 3 informants. Based on the results of the research, it shows that not all Green products in sanitary napkins in the era of the Zillennial generation can be consumed and Ethical living in the life of the Zillennial Generation is still lacking and there is a need for education about environmental hazards, good green products will provide good environmental value . The application of green products and also green marketing in running a business has proven to have an impact on competitive advantage and also on the surrounding business environment. With so many sanitary napkin products, it is hoped that Zillennials will be more aware of, health and the surrounding environment are maintained and it is time for business people to produce green products and implement promotions among Zillennials in stages.